2018
DOI: 10.3892/mmr.2018.9786
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA DLX6‑AS1 is associated with malignant progression and promotes proliferation and invasion in esophageal squamous cell carcinoma

Abstract: Despite being one of the most prevalent and fatal types of cancer worldwide, the biological details of esophageal squamous cell carcinoma (ESCC) remain unknown. Recent studies have demonstrated the crucial roles of long non-coding RNAs (lncRNAs) in diverse biological processes including cancer initiation, progression and metastasis. The aim of the present study was to assess the expression profile of distal-less homeobox 6 antisense RNA 1 (DLX6-AS1) in ESCC tissues and its contributions to ESCC cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Partial reversal of mir-505-3p's carcinogenic effects can be achieved by overpressing Runx2. Wang et al additionally showed that dlx6-as1 triggers its downstream effects on breast cancer cells by downregulating Fus [23]. These ndings indicate that dlx6-as1 promotes breast cancer progression and is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Partial reversal of mir-505-3p's carcinogenic effects can be achieved by overpressing Runx2. Wang et al additionally showed that dlx6-as1 triggers its downstream effects on breast cancer cells by downregulating Fus [23]. These ndings indicate that dlx6-as1 promotes breast cancer progression and is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, an increasing number of studies show that aberrant lncrnas expression leads to the development of many kinds of malignant tumours, including breast cancer [12][13][14][15][16][17][18]. As a kind of lncrnas, dlx6-as1 is believed to be carcinogenic by regulating the progression of renal cell carcinoma, liver cell carcinoma, glioma, pancreatic cancer and lung adenocarcinoma [19][20][21][22][23][24][25][26]. Normal brain tissue has a high expression of DLX6-AS1, which is involved in the development regulation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The capability to regulate cell proliferation and apoptosis is crucial in cancer therapy. Various publications have shown that ncRNAs, such as miRNAs and lncRNAs, mediate ESCC cell proliferation and cell apoptosis or function mutually to regulate cell migration and invasion [59,64,82].…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%